Modeling chemistry in and above snow at Summit, Greenland - Part 2: Impact of snowpack chemistry on the oxidation capacity of the boundary layer - Thomas, Jennie L.; Dibb, J. E.; Huey, L. G.; Liao, J.; Tanner, D.; Lefer, B.; Von Glasow, R.; Stutz, J. (Atmospheric Chemistry and Physics, 2012)
International audience The chemical composition of the boundary layer in snow covered regions is impacted by chemistry in the snowpack via uptake, processing, and emission of atmospheric trace gases. We use the coupled one-dimensional (1-D) snow chemistry and atmospheric boundary layer model MISTRA-SNOW to study the impact of snowpack chemistry on the oxidation capacity of the boundary layer. The model includes gas phase photochemistry and chemical reactions both in the interstitial air and the atmosphere. While it is acknowledged that the chemistry occurring at ice surfaces may consist of a true quasi-liquid layer and/or a concentrated brine layer, lack of additional knowledge requires that this chemistry be modeled as primarily aqueous chemistry occurring in a liquid-like layer (LLL) on snow grains. The model has been recently compared with BrO and NO data taken on 10 June-13 June 2008 as part of the Greenland Summit Halogen-HOx experiment (GSHOX). In the present study, we use the same focus period to investigate the influence of snowpack derived chemistry on OH and HOx + RO2 in the boundary layer. We compare model results with chemical ionization mass spectrometry (CIMS) measurements of the hydroxyl radical (OH) and of the hydroperoxyl radical (HO2) plus the sum of all organic peroxy radicals (RO2) taken at Summit during summer 2008. Using sensitivity runs we show that snowpack influenced nitrogen cycling and bromine chemistry both increase the oxidation capacity of the boundary layer and that together they increase the mid-day OH concentrations. Bromine chemistry increases the OH concentration by 10-18% (10% at noon LT), while snow sourced NOx increases OH concentrations by 20-50% (27% at noon LT). We show for the first time, using a coupled one-dimensional snowpack-boundary layer model, that air-snow interactions impact the oxidation capacity of the boundary layer and that it is not possible to match measured OH levels without snowpack NOx and halogen emissions. Model predicted HONO compared with ...